Multi-Distance Veins Projection Based on Single Axis Camera and Projector System - Gunawan, I Putu Adi Surya; Sigit, Riyanto; Gunawan, Agus Indra (EMITTER International Journal of Engineering Technology, 2019)
Every person has different location of veins, some veins are easily detected because it is visible due to thin tissue, and the other are invisible. This different location of veins causes intravenous access procedures and the procreas of intravenous therapy become longer. Multi-distance vein projections aim to simplify the measurement process where the device and object do not have to be at a certain distance. Some research that has been done especially for real-time vein projection does not conduct how the characteristics of projection at different distances. In this paper, we propose a method for performing multi-distance real-time back-projection by using the intersection between camera and projector. This method equiped with an ultrasonic distance sensor to identify the projection characteristic in any distance. In its implementation, this method is able to project at a distance of 20-40 cm with a maximum projection error of 0.6 mm. The measurement angle tolerance between the object and the device is Â±5 degrees with a maximum error of 0.7 mm.